(untitled) (Hekima Review, 2006)
This study intends to document the rise and development of intercultural biblical exegesis in Africa, especially with regard to the New Testament interpretations. It argues that this new exegetical tool was more decisively launched in 1996, when J.S. Ukpong published an article introducing and applying the method of inculturation biblical hermeneutic. In 1998, J.B. Matand with no reference to J. Ukpong, embraced this method, which evolved into intercultural biblical exegesis/ hermeneutic through the books by A.C.N. Cilumba and C.U. Manus, respectively published in 2001 and 2003. J-C. Loba-Mkole boosted up these efforts in 2005 not only by using intercultural biblical exegesis, but also viewing it as intercultural mediations. The first section of this article briefly presents different trends of biblical exegesis in Africa, while the second one deals with different phases of intercultural exegesis.